2006
DOI: 10.1111/j.1466-7657.2006.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of traditional healers and modern medicine in Ghana

Abstract: Findings indicate that traditional and modern medicines will always be part of Ghanaian healthcare delivery and efforts should be made to integrate traditional practitioners into the national healthcare delivery system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 6 publications
7
91
0
Order By: Relevance
“…Religious influence may also be a contributory factor to reduced access to NTFPs. Roots, herbs, leaves and animals used in traditional medicine are important in the healthcare delivery system in the area, and religious bonds have been found to impact the choices made by individuals seeking healthcare services (Tabi et al, 2006). Traditional medicine consists of health practices, approaches, knowledge and beliefs incorporating animal-or plant-based medicines and spiritual therapies, used either singularly or in combination, to treat, diagnose and prevent illness and to maintain well-being (WHO, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Religious influence may also be a contributory factor to reduced access to NTFPs. Roots, herbs, leaves and animals used in traditional medicine are important in the healthcare delivery system in the area, and religious bonds have been found to impact the choices made by individuals seeking healthcare services (Tabi et al, 2006). Traditional medicine consists of health practices, approaches, knowledge and beliefs incorporating animal-or plant-based medicines and spiritual therapies, used either singularly or in combination, to treat, diagnose and prevent illness and to maintain well-being (WHO, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization in some African countries, 80% of the population depends on traditional medicine for primary health care [3]. African folk medicine is a holistic discipline involving extensive use of indigenous herbalism combined with aspects of African spirituality [4]. In general, the traditional medicine encompasses the use of substances such as herbs, plants, animals and mineral elements, with dosages and practices based on sociocultural norms and religious beliefs as well as witnessed experiences and observation of a specific group, namely traditional healers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence seems to indicate that traditional healers, herbalists and birth attendants in African societies [19], have always maintained this tradition. Similar studies have concluded that traditional methods of protecting infants/children from diseases were still common in developing countries [20]. The analysis of our data suggests that Mali has a pluralistic medical system where biomedical and traditional medical systems coexist.…”
Section: Use Of Traditional Medicines For Child Health Care During Thmentioning
confidence: 49%